2023
DOI: 10.18421/tem121-56
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Prospective Digital Transformation Adopters: An Extended Diffusion of Innovations Theory

Abstract: This study investigated the effects of factors that influence users' perceptions to adopt digital transformation. Eight hypotheses were proposed and tested employing the Structural Equation Modeling. 248 government personnel, instructors, and students were recruited to answer the questionnaires through Google Form. The experimental results indicated that facilitating conditions, policy, social influence, and knowledge all had a positive and significant impact on digital transformation adoption. Meanwhile, poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…The Awareness factor highlights the importance of raising awareness among participations about the benefits of digital training programs. This finding is consistent with prior research that has identified the need for effective communication(Huong & Duc, 2023). The Knowledge factor in our study suggests that the acquisition of knowledge and skills is a key component of effective digital training programs.…”
supporting
confidence: 92%
“…The Awareness factor highlights the importance of raising awareness among participations about the benefits of digital training programs. This finding is consistent with prior research that has identified the need for effective communication(Huong & Duc, 2023). The Knowledge factor in our study suggests that the acquisition of knowledge and skills is a key component of effective digital training programs.…”
supporting
confidence: 92%